Advancing Formative Assessment in Every Classroom : a Guide for Instructional Leaders, 2nd Ed. - Moss, Connie M. (Association for Supervision & Curriculum Development, 2019)
The updated 2nd edition of this practical resource guides school leaders in working with teachers to make formative assessment an integral part of their classrooms.